DEVELOPING CREATIVEECONOMY FOR COMMUNITY LEARNERS IN SUPPORTING TOURISM IN TEMBOK AND ABANG VILLAGE, BALI - Sudita, I Ketut; Sudana, Dewa Nyoman; Suandi, I Nengah; Sanjaya, Dewa Bagus (International Journal of Social Science and Business, 2017)
Community group learners are a community group that  sets an example and deserves to be given a priority in a program for strengthening and  extending economy, especially in Bali province.  Departing from this idea, this study was aimed  (1) to produce an innovative   design  for handicrafs (creative economy)  for community group learners which matches their existing potentialities, (2) to produce a creative economy strategy at a larger scale. The results of this study showed that  the craftsmen had been able to produce  various  handicrafts such as laptop baggage, sokasi (bamboo basketwork used for holding rice), ballpoint stand, bamboo basket or tray for keeping offerings with  a variety of  designs. Community learners were able to develop product to meet the market conditions and   demands and were able to develop a larger network, with the local government, universities, and  businesses.